Correlated ab initio study of nucleic acid bases and their tautomers in the gas phase, in a microhydrated environment and in aqueous solution. guanine: surprising stabilization of rare tautomers in aqueous solution - Hanus, Michal; Ryjácek, Filip; Kabelác, Martin; Kubar, Tomás; Bogdan, Tetyana V; Trygubenko, Semen A; Hobza, Pavel (Journal of the American Chemical Society, 2003)
Altogether eight keto and enol tautomers of guanine were studied theoretically in the gas phase, in a microhydrated environment (1 and 2 water molecules) and in bulk water. The structures of isolated, as well as mono- and dihydrated tautomers were determined by means of the RI-MP2 method using the extended TZVPP (5s3p2d1f/3s2p1d) basis set. The relative energies of isolated tautomers included the correction to higher correlation energy terms evaluated at the CCSD(T)/aug-cc-pVDZ level. The relative enthalpies at 0 K and relative free energies at 298 K were based on the above-mentioned relative energies and zero-point vibration energies, temperature-dependent enthalpy terms and entropies evaluated at the MP2/6-31G level. The keto form having hydrogen atom at N7 is the global minimum while the canonical form having hydrogen atom at N9 represents the first local minimum at all theoretical levels in vacuo and in the presence of 1 and 2 water molecules. All three unusual rare tautomers having hydrogens at N3 and N7, at N3 and N9, and also at N9 and N7 are systematically considerably less stable and can be hardly detected in the gas phase. The theoretical predictions fully agree with existing theoretical as well as experimental results. The effect of bulk solvent on the relative stability of guanine tautomers was studied by self-consistent reaction field and molecular dynamics free energy calculations using the thermodynamic integration method. Bulk solvent, surprisingly, strongly favored these three rare tautomers over all remaining low-energy tautomers and probably only these forms can exist in water phase. The global minimum (tautomer with hydrogens at N3 and N7) is by 13 kcal/mol more stable than the canonical form (3rd local minimum). Addition of one or two water molecules does not change the relative stability order of isolated guanine tautomers but the respective trend clearly supports the surprising stabilization of three rare forms.
Keywords: voda; roztoky; termodynamika; Gases; Solutions; Guanine; chemické modely; guanin; Water; Models, Chemical; Thermodynamics; plyny